ANALISIS SINYAL ELEKTRONEUROMIOGRAFI (EMG) UNTUK KEPERLUAN DIAGNOSIS KLINIS BERBASIS NEURAL NETWORK - , Erlinasari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Electromyography (EMG) is a study of the electrical activity generated by muscles]. Muscle disorder that can be recorded on the most popular clinical EMG signal are nerve disorders (neuropathy) and muscle disorders (myopathy). This study tries to analyze the EMG signal feature extraction from healthy people and from patients with neuropathy and myopathy patients meeting the power spectral techniques (power spectrum density, PSD). Furthermore PSD value of each type of input EMG into back propagation neural network to recognize or classify three types of EMG signals. Neural networks that have been made are only tested by adding some noise in the EMG signal.